Selective monoalkylation of hydroquinone in the presence of SO3H-functionalized ionic liquids as catalysts - Bhongale, Priyanka V.; Joshi, Sunil S.; Mali, Nilesh A. (Chemical Papers, 2020)
A process aiming atO-alkylation of hydroquinone (HQ), where ionic liquids (ILs) act as catalyst is objectively described. Five SO3H-functionalized ILs having different cations were prepared and characterized by NMR and FTIR techniques. The acidity and thermal stability of ILs were determined by Hammett function and thermogravimetric analysis (TGA), respectively. The catalytic activity of these ILs were tested forO-alkylation of HQ with methanol in 4-methoxyphenol (4MP) in the presence of small amount of benzoquinone (BQ). The effect of reaction parameters such as temperature, time, catalyst loading and substrate concentration on the conversion of HQ and product distribution was examined and optimized to maximize the yield of 4MP using 1,3-disulfonic acid imidazolium hydrogen sulfate (IL2) catalyst. Maximum yield of desired product 4MP 93.79% was obtained at 338 K temperature, 5.45 x 10(-2) mol HQ, 8.33 x 10(-3) mol BQ, and 10.37 mol% catalyst loading in 120 min reaction time. Single-product formation was observed up to 338 K temperature but higher temperature (above 338 K) and longer reaction time resulted in the formation of 2,4-dimethoxyphenol (24DMP) as a by-product. Catalyst recyclability was also established up to the fifth run which showed no declination in its activity.
Keywords: 4-Methoxyphenol; Benzoquinone; Hydroquinone; ionic liquids; O-alkylation

Kinetic study on alkylation of hydroquinone with methanol over SO3H functionalized Bronsted acidic ionic liquids - Bhongale, V. Priyanka; Amonkar, Amogh A.; Joshi, Sunil S.; Mali, Nilesh A. (Canadian Journal of Chemical Engineering, 2022)
O-alkylation of a dihydric phenol (i.e., hydroquinone) with methanol in presence of benzoquinone catalyzed by double SO3H functionalized Bronsted acidic ionic liquids (i.e., 1,3-disulphonic acid imidazolium hydrogen sulphate, 1,3-disulphonic acid benzimidazolium hydrogen sulphate, and sulphuric acid) is studied in a batch reactor. The sensitivity of activity and selectivity with reaction time, temperature, speed of agitation, and catalyst loading was examined. The plausible reaction pathways proposed based on the experimental observations and detailed kinetic investigation are performed by assuming a homogeneous reaction phase. The kinetic parameters, such as pre-exponential factor and activation energy, are estimated for both ionic liquids and sulphuric acid by considering all competitive reactions, and comparative results were presented. An extended form of the Arrhenius equation is used to estimate the kinetic parameters for the reaction which showed curvature in lnk against a 1/T plot. The model prediction with the estimated kinetic parameters is in good agreement with the experimental data, which confirmed the model validity in the experimental operating range. It was found that ionic liquid has a potential application in the synthesis of a selective monoalkylated product of hydroquinone. The kinetic analysis performed is found to be useful in the understanding of process behaviour.
Keywords: 4-Methoxyphenol; Hydroquinone; ionic liquids; Kinetic analysis; O-alkylation